Chemically triggered drug release from an antibody-drug conjugate leads to potent antitumour activity in mice - Raffaella Rossin (Nature Portfolio, 2018)
Current antibody-drug conjugates (ADCs) target internalising receptors on cancer cells. Here, the authors report the development and in vivo validation of a non-internalising ADC with the capacity to target cancer cells and release its therapeutic cargo extracellularly via a chemical trigger.